Clinical research on RSV prevention in children and pregnant women: progress and perspectives - Gong, Xuejia; Luo, Erdan; Fan, Li; Zhang, Wanggang; Yang, Yan; Du, Yuhua; Yang, Xiao; Xing, Shasha (Frontiers in Immunology, 2024)
Respiratory syncytial virus (RSV) is a significant causative agent of bronchitis and pneumonia in infants and children. The identification and structural analysis of the surface fusion glycoprotein of RSV represents a pivotal advancement in the development of RSV prevention. This review provides a comprehensive summary of RSV monoclonal antibody (mAb) and vaccine clinical trials registered on ClinicalTrials.gov, emphasizing on the classification, name, target, phase, clinical outcomes, and safety data of RSV vaccination in newborns, infants and children. We also discuss the characteristics of the types of RSV vaccines for maternal immunity and summarize the current clinical research progress of RSV vaccination in pregnant women and their protective efficacy in infants. This review will provide new ideas for the development of RSV prevention for children in the future.